Ectopic breast fibroadenoma of the vulva: a case report - He, Yixiao; Xie, Gang; Ji, Yuzhu; Shi, Yu; He, Yushuang; Lei, Xue (Frontiers in Oncology, 2025)
BackgroundVulvar ectopic breast fibroadenoma (EBF) is an exceptionally rare benign neoplasm that lacks distinctive clinical or radiological features rendering pre-operative differentiation from other vulvar masses challenging. Definitive diagnosis requires histopathological confirmation. Two non-exclusive histogenetic hypotheses have been proposed: (1) derivation from ectopic breast tissue along the embryonic “milk line,” (2) origin from hormonally responsive anogenital mammary-like glands with latent potential for benign or malignant transformation.Case presentationA 41-year-old woman presented with an incidentally discovered, slowly enlarging, painless right vulvar mass. Ultrasonography revealed a well-circumscribed hypoechoic nodule. Complete surgical excision was performed, and histopathological evaluation—including immunohistochemistry for estrogen receptor, progesterone receptor, GATA3, and p63—confirmed ectopic breast fibroadenoma. No recurrence was detected at 3-month follow-up.ConclusionDespite its rarity, vulvar EBF must be considered in the differential diagnosis of vulvar masses in reproductive-age women. En-bloc excision is curative; however, long-term surveillance is warranted to monitor for hormone-driven recurrence or malignant evolution.